IMPROVING THE DIGITALPRENEUR POTENTIAL OF ECONOMIC EDUCATIONAL STUDENTS OF JENDERAL SOEDIRMAN UNIVERSITY - Perwita, Dyah; Widuri, Retno; Afif, Nur Choirul; Hadi, Prisilia (STKIP Persada Khatulistiwa Sintang, 2024)
Higher education is the most appropriate level of formal education to prepare generations with an entrepreneurial spirit. The entrepreneurial potential contained in students must be maximized to create new businesses that are in line with current developments. This study aims to improve the potential of digital entrepreneurs (digipreneurs) in economic education students at Jenderal Soedirman University so that they can contribute to reducing the number of unemployed and increasing economic growth through the creation of new jobs, especially in the education sector. This study used a qualitative approach. Data collection techniques using interviews, observation, questionnaires, and documentation. The data source used uses primary data or data obtained directly from data sources without intermediaries. The results of the study illustrate that economics education students have increased potential to become digitalpreneurs in the education sector. Apart from that, this increase in potential reflects concepts and plans to be realized and developed in accordance with current developments. The increase in digitalpreneur business potential among economic education students can be measured using the indicator such as innovativeness, proactiveness, risk taking, competitive aggressiveness, and autonomy.